Gapos - Mateo, Mary Laddie C.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
Society is constituted by institutions. These institutions establish and influence the laws, practices, and customs in every model society. They in turn become society's conventions that guide humans to the right and proper direction. Of course, these institutions define to an extent human behavior. Metaphorically speaking, I believe that these institutions direct function in society as strings direct movement in things. Strings lead and tug. So do laws, practices, and customs. Society's conventions may guide the people to the right path, like how a leashed, trained dog guides its blind master. They bind people to unity, like how a wedding cord may bind husbands and wives to love and matrimony. On the other hand, conventions may constrain people to do things against what might be their nature, like how a tied balloon is kept by the string in its ascent, or they may try to manipulate people, like how a puppeteer leads a puppet. Figuratively, conventions are invisible strings attached to humans. They guide and unite, constrain and manipulate human society. Some may just be content and happy with rules. Some, on the other hand, may be smothered and limited by too much of what convention demands. Because of these, some may want to remain attached to the strings. While others may want to break free of them.
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman
Keywords: Societies -- Philippines